CARTOGRAPHIC MISTAKE IN THE MUNICIPAL BOUNDARIES BETWEEN NOVA COLINAS AND RIACHÃO IN MARANHÃO - Carneiro Ferreira, Edinaiane (Journal of Interdisciplinary Debates, 2025)
This paper analyzes the municipal boundaries between Nova Colinas and Riachão in southern Maranhão. The study discusses a cartographic misunderstanding between the municipalities of Nova Colinas and Riachão in the state of Maranhão. This involves identifying and understanding land use and occupation conflicts and territorial management in the border areas between the two municipalities, considering the socioeconomic and environmental implications arising from this dynamic. This issue is justified by the need for integrated and sustainable natural resource management, which minimizes conflicts between different land uses and occupations and promotes regional development. The central objective of this study is to analyze the land cover characteristics in the border areas and identify the main land use and occupation conflicts. The research conducted in these neighboring municipalities focused primarily on analyzing territorial overlaps and conflicts arising from land use and occupation. The study sought to understand the socioeconomic and environmental implications of natural resources, minimize conflicts through the final research results, and promote regional development. To this end, the following procedures were employed: a bibliographic survey of legislation and public policies related to land use and occupation in the two municipalities; analysis of satellite imagery and aerial photographs to map land cover; data from the latest 2022 IBGE Demographic Census; a Garmin Etrex 22x GPS unit; and QGis software version 3.40; and consultation with local authorities and public agencies such as the IBGE (Brazilian Institute of Statistics and Geography), ALEMA (MARANHÃO STATE LEGISLATIVE ASSEMBLY), and IMESC (Maranhão Institute of Socioeconomic and Cartographic Studies).